The Effect of R&D Expenditure on CO2 Emissions in Austria - Bhenu Artha; Bahri Bahri; Ardhi Khairi; Fernando Fernando (Journal of Business and Management Review, 2021)
The developed financial sector can significantly provide financial services to developing economies by the motive as well as best opportunity of using new advanced technology; it may help them to maintain clean environment with help of environmentally friendly production, thus providing with a higher level of the global environmental quality and further it will boost sustainable development of economies (J. Frankel & Rose, 2002). Financial development would increase R&D investment as to speed up growth, thereby influencing the environmental quality (J. A. Frankel & Romer, 1999). The objective of this research is to determine the effect of R&D expenditure on CO2 emissions in Austria in 1996-2006. We presented a quantitative study using simple linear regression to analyze the data and as a result of this process, we found that R&D expenditure has significant effect to CO2 emissions in Austria in 1996-2006. The fact that R&D influence on CO2 emissions can be positive, negative and insignificant must be taken into account when designing environmental policies and various programs, strategies and initiatives to encourage and fund R&D activities, in the context of environmental protection, government efforts should be strictly focused on the promotion and support of R&D programs directly aimed at reducing CO2 emissions and increasing the use thereof (Petrović & Lobanov, 2020).